Alternate assessment of strength characteristics of clayey soil for compaction using ultrasonic pulse velocity method - A, Vinay; A.V.Pradeepkumar, Dr; M.R Rajashekhara, Dr (International Journal of Engineering and Technology, 2018)
Earthwork is a component in any Civil Engineering construction and to determination of soil properties in the laboratory is the basis of design. Clayey soils exhibits large volume changes in presence of water leads to swelling and shrinkage. Soils used for construction should satisfy two important properties like less settlement and more shear strength. Present investigation deals with the determination of compaction characteristics of clayey soil by an alternate method of assessment like pulse velocity method which is more accurate and fast compared to conventional methods. Laboratory compaction soil samples prepared at different water content by standard and modified proctor, compaction method was used to determine the ultrasonic pulse velocity at different water contents. The variation of velocity with respect to water content was correlated. Ultrasonic pulse transmitted from one side of the sample was received at the other end and was used in calculating soil properties. It was observed that with increase in water content the density increases and ultrasonic pulse velocity also increases. Standard proctor method of compaction and modified proctor moulds was used for compaction and 5 trails were done with variation in water content to get compaction curve, so as to find the variation of strength to stabilization and its variation by Ultrasonic pulse velocity technique.